2001
DOI: 10.1007/s101570170030
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal effects of short-term prednisolone therapy in children with steroid-responsive nephrotic syndrome

Abstract: Background. Osteoporosis or bone fracture can be induced in nephrotic children treated long-term with high doses of glucocorticoids. The purpose of this study was to determine whether short-term prednisolone therapy affects the skeleton in children with steroid-responsive nephrotic syndrome (NS). Methods. Bone mineral density (BMD) and biochemical parameters of mineral and skeletal homeostasis in nine children (four girls, five boys) aged between 2 and 7 years at the first episode of NS were measured. Predniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Kano et al [18] observed osteocalcin levels 8 weeks after the alternate phase and showed increasing from 6.7±2.6 µg/l to 15.0±6.4 µg/l. As mentioned previously that study of osteocalcin levels after 4 weeks the alternate phase in NS patients have not been evaluated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kano et al [18] observed osteocalcin levels 8 weeks after the alternate phase and showed increasing from 6.7±2.6 µg/l to 15.0±6.4 µg/l. As mentioned previously that study of osteocalcin levels after 4 weeks the alternate phase in NS patients have not been evaluated.…”
Section: Discussionmentioning
confidence: 97%
“…Osteocalcin levels of initial attack, infrequent relapses, frequently relapsing, and dependent steroid NS at t=0, t=1, t=2 were not significantly different because patients were given the same dose. Kano et al [18] reported osteocalcin levels of children with steroidresponsive NS 4 weeks after starting prednisolone therapy (induction phase) decreased 68.54%. The other study that was reported by Mohamed and Abdul-Latif [19], osteocalcin levels decreased 30.59% after 1 month of therapy in the initial attack NS.…”
Section: Discussionmentioning
confidence: 99%
“…Although FRNS subgroup had higher number of relapses, longer steroid therapy, and greater cumulative steroid, this occurrence might be caused by the longer relapse free interval of FRNS subgroup. As Kano et al 19 stated, the decrease of lumbal bmD after 16 weeks short-term prednisolone therapy were transient and would normalize by 16 weeks after the cessation of therapy. So, this might explain the results, since the relaps free interval median of FRNS group were 28 weeks while median of IRNS group were only 8 weeks.…”
Section: Discussionmentioning
confidence: 97%